Physicochemical and antimicrobial effects of gelatin-based edible films incorporated with garlic peel extract on the rainbow trout fillets - Ucak, Ilknur (Progress in Nutrition, 2019)
Influence of gelatin-based edible films incorporated with garlic peel extract (GPE) with concentration of 4% and 8% (by volume per mass of gelatin) on the microbiological, sensorial and physicochemical quality of rainbow trout fillets during refrigerated storage at 4+-1 centigrade were evaluated. Gelatin films enriched with GPE retarted the total mesophilic and total psychrophilic bacteria, and Enterobacteriaceae counts during the storage period. Compared to control samples, lipid oxidation was delayed in the samples wrapped with gelatin films incorporated with GPE, especially in concentration of 8%. The sensory results are correlated with physicochemical and microbiological results. The shelf-life of rainbow trout fillets was found 5 days for control and the fillets wrapped with gelatin film without GPE, respectively, while the shelf life of fish was 10 days for the fillets wrapped with gelatin film incorporated with GPE. According to results of the study, the incorporation of GPE into gelatin film could enhance the both antimicrobial and antioxidative characteristics of the film. Therefore, gelatin film enriched with GPE efficient in maintaining the qualities of the rainbow trout fillets during refrigerated storage.